Effectiveness of papaya seed as adsorbent for removal of Pb(II) from aqueous solution: article - Jaafar, Nurtasha Atikah; Jafri, Hasnora (2018)
The used of papaya seed, fruit waste as the low-cost adsorbent was investigated as replacement for current costly methods of removing metals ions from aqueous solution. The removal of Pb(II) ions from aqueous solution onto physically and chemically treated papaya seed were studied at varying pH of metal ion solution (pH 3 – pH 5), adsorbent dose ( 0.06 g – 0.10 g) and contact time (15 minutes – 45 minutes) in batch mode. In chemically treated of papaya seed, the acetic acid was used as chemical activating agent to enhance the adsorption capacity of Pb(II) ions onto the adsorbent. Papaya seed from physically treated and chemically treated were also calcined at different temperature of 300°C, 400°C and 500°C to see its effect on surface area and pore size of adsorbent. Batch experiment were carried out to evaluate the adsorption capacity of Pb(II) ions onto papaya seed. The residual Pb(II) ions concentration after adsorption was analyzed using Atomic Absorption Spectroscopy (AAS). Characterization study on surface area and functional group of papaya seed were using Brunauer- Emmett- Teller (BET) and Fourier Transform Infrared (FTIR) respectively. The optimum pH for physically treated and chemically treated papaya seed were achieved at pH 3 and pH 5 respectively. Results indicates the removal efficiency for Pb(II) was about 99% using both treated papaya seed at adsorbent dose 0.10 g. The equilibrium was achieved at 15 minutes which the adsorption become saturated to maximum uptake capacity. Based on three parameter studied, chemically treated papaya seed at 500°C was the best adsorbent on the Pb(II) removal in aqueous solution.